A Sixteen Thousand Year Old Organic Deposit, Northern Baffin Island, N.W.T., Canada: Palynology and Significance - Short, Susan; Andrews, John (Géographie physique et Quaternaire)

(untitled) (Les Presses de l'Université de Montréal, 1988)
ABSTRACTA 3 m exposure of sediment containing organics was sampled near the settlement of Arctic Bay, Baffin Island, N.W.T. A total of seven radiocarbon dates have been obtained from the deposit. Three dates between 182.5 and 290 cm depth gave radiocarbon ages between 14,185 ± 760 and 16,849 ± 860. A date from 82.5 to 87.5 cm resulted in an age of 8635 ± 565. An apparent reversal in 14C dates may reflect folding of the sediments associated with the downslope creep of the deposit or rapid accumulation of organics. The three basal dates are the first terrestrial sediments from Baffin Island to date from older than ca. 10,000 BP and less than 20,000 BP. Analysis of the sediment for pollen indicated that it is generally sparse. The pollen assemblage is dominated by Salix, Cyperaceae, and Gramineae pollen and exotic pollen types {Pinus, Picea, Betula, and Alnus) occur sporadically throughout the section.